2019
DOI: 10.1177/0046958019895897
|View full text |Cite
|
Sign up to set email alerts
|

Provincial and Age Disparity on Chronic Disease Education Among Migrants in China: The Migrants Population Dynamic Monitoring Survey

Abstract: Chronic diseases have become serious threats to public health in China; the risk is particularly high for internal migrants. Chronic disease education is a key to the prevention and control of chronic diseases for such population. The national population-based Migrants Population Dynamic Monitoring Survey (MPSMA) was used to examine the current status and delivery methods of chronic disease education among internal migrants, from both provincial level and individual’s level. The study population included 402 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Although NEPHS deployment level has risen rapidly in recent years [9], there is still a signi cant gap in the national target, and the underlying factors need to be revealed. Some recent studies have con rmed that gender, education, community type, migration range (MR) and regional economic development level (REDL) have signi cant impacts on the IMs' NEPHSU [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although NEPHS deployment level has risen rapidly in recent years [9], there is still a signi cant gap in the national target, and the underlying factors need to be revealed. Some recent studies have con rmed that gender, education, community type, migration range (MR) and regional economic development level (REDL) have signi cant impacts on the IMs' NEPHSU [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The new situation promotes the government's working mode to change from ooding to precise [8], and the focus has gradually shifted to how to achieve the NEPHS equalization within the IMs. Recent studies have con rmed that sex, education, community type, migration range (MR) and regional economic development level (REDL) have signi cant impacts on IMs' NEPHS [3,9,[10][11][12][13][14][15]. Studies have consistently concluded that the NEPHS utilization of inter-provincial IMs is lower than that of intra-provincial IMs [9,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The new situation promotes the government's working mode to change from ooding to precise [8], and the focus has gradually shifted to how to achieve the NEPHS equalization within the IMs. Recent studies have con rmed that sex, education, community type, migration range (MR) and regional economic development level (REDL) have signi cant impacts on IMs' NEPHS [3,9,[10][11][12][13][14][15]. Studies have consistently concluded that the NEPHS utilization of inter-provincial IMs is lower than that of intra-provincial IMs [9,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%